Biological sciences, social sciences and the languages of stress. Issue 2 (4th March 2018) - Youdell, Deborah; Harwood, Valerie; Lindley, Martin R.
ABSTRACT: There are well documented concerns with the imposition of high stakes testing into the fabric of school education, and there is now an increasing focus on how such tests impact children's 'well-being'. This can be witnessed in reports in the popular news media, where discussion of these impacts frequently refer to 'stress' and 'anxiety'. Yet, there is no work that is able to tell us about what is happening in the bodies of the teachers and children who are living this schooling in the day-to-day; whether this is best considered through the languages of 'stress'; or what the implications – emotional, educational, embodied – of these experiences might be. This paper develops a transdisciplinary approach that brings social and biological accounts together in order to address the 'more-than-social' of the emotionality of childhood and schooling. We seek out opportunities for transdisciplinary connectivity and for new ways of seeing and knowing about learning. We consider what these ways of seeing and knowing might offer to education.